Performance of a Solar Water and Space Heating System Employing Collector with Colour Absorber - Kalogirou, Soteris A.; Tripanagnostopoulos, Yiannis; Souliotis, Manolis (My University, 2004)
To avoid the monotony of the black colored flat plate solar collectors we can use absorbers of blue, red-brown, green or other color. Because of the lower collector absorptance these collectors have lower thermal efficiency than that of the usual black type collectors, they are however of more interest to architects for applications on traditional or modern buildings. In this paper a solar hot water and space heating application with colored-absorber collectors of high (usual type) and low (selective) emissivity is presented and analyzed with respect to their performance. The house considered is 150 m2 insulated construction with a UA value of 1200 kJ/hr°C, kept at 21°C. The solar system consists of solar collectors with total aperture area of 50 m2 and a 3000 lt storage tank. The solar system provides part of the heating load and satisfies also the hot water needs of a 4-persons family. The system is simulated with TRNSYS on an annual basis at three different locations, Nicosia, Cyprus; Athens, Greece and Madison, Wisconsin. The first two locations represent locations with hot summer and mild winters, whereas the latter represents a location with mild summer and severe winter and was considered for comparison purposes. The results show that the energy output depends on the absorber darkness. For a medium value of the coefficient of absorptance, the colored collectors give satisfactory results with respect to the drop of the amount of collected energy, compared to collectors with black absorbers. This implies the use of slightly larger collector aperture area to have the same energy output as that of typical black colored collectors, which is acceptable comparing the aesthetic improvement of the solar system.
Keywords: Colored absorber; Solar collector; Water heating; Space heating; Industrial process heat